Refeeding Syndrome: A Review - Alam, ABM Shahidul; Karim, ASM Bazlul; Sadat, S Anwar (Bangladesh Journal of Child Health, 2010)
Refeeding syndrome (RS) was first described among prisoners of far east after the second world war. Eating again after a long period of prolonged starvation seems to precipitate cardiac failure. It develops in malnourished patient who receives nutritional support after a long period of inadequate intake. It usually develops within four days of initiation of dietary therapy. Although no consensus definition exists, refeeding syndrome can be defined as the consequences of severe fluid and electrolyte shifts in malnourished patient when they are refed. It can develop after oral, enteral (through a tube) or parenteral (Intravenous) nutritional therapy. Phosphate plays an important role in the pathogenesis of various manifestations of refeeding syndrome. The biochemical hall mark of refeeding syndrome is hypophosphataemia. DOI: 10.3329/bjch.v33i1.5672 Bangladesh Journal of Child Health 2009; Vol.33(1): 27-30